2023
DOI: 10.3390/app13042406
|View full text |Cite
|
Sign up to set email alerts
|

Research on Stability Evaluation of Perilous Rock on Soil Slope Based on Natural Vibration Frequency

Abstract: Perilous rock instability on the soil slope brings a substantial threat to project operation and even people’s lives. The buried depth of the perilous rock is a challenge to deal with and primarily determines its stability, and the indirect rapid identification of its buried depth is the key to its stability evaluation. The paper aims to find a new and quick method to measure the buried depth of perilous rock on the soil slope and to solve the hard-to-measure buried depth stability evaluation. When the damping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In fact, the proposed procedure simply requires, together with a first susceptibility model, a status slope unit check for a small percentage of the study area and systematic mapping in one or more smaller subareas. The study was focused on slide and flow landslide typologies, but the strategies of analysis can also be helpful for increasing landslide archives and related resolution of landslide susceptibility maps for any other type of landslide (such as falls, topples, and deep-seated typologies) with the aim of identifying areas to be analyzed at a larger scale through the application of empirical or analytical models for rockfalls (e.g., [57][58][59]) or to assess the magnitude and deformations rate for other slower and more complex landslides (e.g., [60,61]).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the proposed procedure simply requires, together with a first susceptibility model, a status slope unit check for a small percentage of the study area and systematic mapping in one or more smaller subareas. The study was focused on slide and flow landslide typologies, but the strategies of analysis can also be helpful for increasing landslide archives and related resolution of landslide susceptibility maps for any other type of landslide (such as falls, topples, and deep-seated typologies) with the aim of identifying areas to be analyzed at a larger scale through the application of empirical or analytical models for rockfalls (e.g., [57][58][59]) or to assess the magnitude and deformations rate for other slower and more complex landslides (e.g., [60,61]).…”
Section: Discussionmentioning
confidence: 99%
“…Xie et al (2021) established a three-dimensional (3-D) analysis method for the rock vibration, and they proved the effectiveness for the rock stability analysis based on the natural frequency. At present, investigations on the natural frequency of rock primarily concentrate on the field or laboratory scales, such as seismic failure of rock slopes (Song et al 2019a) and rock block's instability (Jia et al 2017(Jia et al , 2019(Jia et al , 2023b, which are characterized by much smaller pores relative to the size of a rock to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…Xie et al found that a ground-penetrating radar (GPR) survey can be used to evaluate the slope stability [29]. Du et al and Jia et al further conducted experimental research on dumping perilous rock and found that the natural vibration frequency is closely related to the stability [30][31][32][33]. However, the above research has just started and is in the experimental stage, and the theory has not yet been perfected [34,35].…”
Section: Introductionmentioning
confidence: 99%